Gender identity and HIV risk among men who have sex with men in Cape Town, South Africa. Issue 11 (2nd November 2018) - Jobson, Geoffrey; Tucker, Andrew; de Swardt, Glenn; Rebe, Kevin; Struthers, Helen; McIntyre, James; Peters, Remco
ABSTRACT: Gender identity plays a potentially important role contributing to HIV risk among MSM in South Africa. Where studies have included a focus on gender identity, MSM reporting gender non-conformity have been found to have a higher risk of being HIV positive than other MSM. This article examines HIV risk among gender non-conforming MSM in a sample of 316 MSM in Cape Town, South Africa. Reporting gender non-conformity was associated with higher HIV prevalence and increased HIV risk behaviour. Gender non-conformity was also associated with a higher likelihood of being unemployed and reporting low household incomes. These findings highlight the importance of gender-identity as a factor affecting access to HIV treatment, care, and prevention in South Africa and this is an issue that needs to be addressed in interventions targeting MSM populations.